Effectiveness of Neutrophil-Lymphocyte Ratio (NLR) as a Marker of Delirium Tremens in Alcohol Use Disorder Patients: A Meta-Analysis - Kusumadewi, Andrian Fajar; Aditya Humar Pradipta (Archives of The Medicine and Case Reports, 2024)
Delirium tremens (DT) is a serious complication of alcohol use disorder (AUD) with a poor prognosis. Early identification of DT is essential for appropriate clinical management. Neutrophil-lymphocyte ratio (NLR) has been proposed as a potential inflammatory biomarker for DT. This study aims to evaluate the effectiveness of NLR as a marker of DT in AUD patients through meta-analysis. A literature search was conducted in the PubMed, Scopus, and Web of Science databases to identify observational studies evaluating NLR in AUD patients with and without DT. Studies that met the inclusion criteria had their data extracted and analyzed using a random effects model. Subgroup analyzes were performed based on gender, age, and AUD severity. Twenty studies (n=2850 patients) were included in the meta-analysis. Results showed that NLR was significantly higher in AUD patients with DT compared with AUD patients without DT (standardized mean difference [SMD] = 1.45; 95% confidence interval [CI] = 1.12-1.78; p < 0.001). Subgroup analyzes showed that these effects were consistent across subgroups. NLR is an effective inflammatory marker for identifying AUD patients with DT. The use of NLR can help in early diagnosis and better management of DT, thereby improving the prognosis of AUD patients.